Differential changes in vascular mRNA levels between rat iliac and renal arteries produced by cessation of voluntary running. Issue 1 (25th July 2012) - Padilla, Jaume; Jenkins, Nathan T.; Roberts, Michael D.; Arce‐Esquivel, Arturo A.; Martin, Jeffrey S.; Laughlin, M. Harold; Booth, Frank W.
Abstract : Early vascular changes at the molecular level caused by adoption of a sedentary lifestyle are incompletely characterized. Herein, we employed the rodent wheel‐lock model to identify mRNAs in the arterial wall that are responsive to the acute transition from higher to lower levels of daily physical activity. Specifically, we evaluated whether short‐term cessation of voluntary wheel running alters vascular mRNA levels in rat conduit arteries previously reported to have marked increases (i.e. iliac artery) versus marked decreases (i.e. renal artery) in blood flow during running. We used young female Wistar rats with free access to voluntary running wheels. Following 23 days of voluntary running (average distance of ∼15 km per night; ∼4.4 h per night), rats in one group were rapidly transitioned to a sedentary state by locking the wheels for 7 days ( n = 9; wheel‐lock 7 day rats) or remained active in a second group for an additional 7 days ( n = 9; wheel‐lock 0 day rats). Real‐time PCR was conducted on total RNA isolated from iliac and renal arteries to evaluate expression of 25 pro‐atherogenic and anti‐atherogenic genes. Compared with the iliac arteries of wheel‐lock 0 day rats, iliac arteries of wheel‐lock 7 day rats exhibited increased expression of TNFR1 (+19%), ET1 (+59%) and LOX‐1 (+31%; all P < 0.05). Moreover, compared with renal arteries of wheel‐lock 0 day rats, renal arteries of wheel‐lock 7 day rats exhibited decreased expression of ETb (−23%), p47phox (−32%) and p67phox (−19%; all P < 0.05). These data demonstrate that cessation of voluntary wheel running for 7 days produces modest, but differential changes in mRNA levels between the iliac and renal arteries of healthy rats. This heterogeneous influence of short‐term physical inactivity could be attributed to the distinct alteration in haemodynamic forces between arteries.